Contribution of Stretch-Induced Force Enhancement to Increased Performance in Maximal Voluntary and Submaximal Artificially Activated Stretch-Shortening Muscle Action - Groeber, Martin; Stafilidis, Savvas; Seiberl, Wolfgang; Baca, Arnold (Frontiers in Physiology, 2020)
In everyday muscle action or exercises, a stretch-shortening cycle (SSC) is performed under different levels of intensity. Thereby, compared to a pure shortening contraction, the shortening phase in a SSC shows enhanced force, work and power. Besides others, one mechanism to explain this ‘SSC-effect’ is referred to the phenomenon of stretch-induced increase in muscle force (known as residual force enhancement; rFE). It is unclear to what extent the intensity of muscle action influences the contribution of rFE to the SSC performance enhancement. Therefore, we examined the torque, knee kinematics, m. vastus lateralis fascicle length and pennation angle changes of thirty healthy adults during isometric, shortening (CON) and stretch-shortening (SSC) conditions at the quadriceps femoris. We conducted maximal voluntary contractions (MVC) and submaximal electrically stimulated contractions at 20%, 35% and 50% of MVC. Isometric trials were performed at 20° knee flexion (straight leg: 0°), and dynamic trials in CON and SSC condition followed dynamometer driven ramp profiles of 80-20° and 20-80-20°, respectively, at an angular velocity set to 60 °/s. Mechanical work during shortening was significantly (p < 0.05) enhanced by up to 21% for all SSC conditions compared to pure CON contractions at the same intensity. Regarding the steady-state torque after the dynamic phase, we found significant torque depression for all submaximal SSCs compared to the isometric reference contractions. There was no difference in the steady-state torque after the shortening phases between CON and SSC conditions at all submaximal intensities, indicating no remaining effect of stretch-induced rFE. In contrast, during MVC efforts the steady-state torque after SSC was significantly less depressed compared to the steady-state torque after the CON condition (p=0.019, η² = 0.239), without significant differences in the m. vastus lateralis fascicle length and pennation angle. From these results, we concluded that the contribution of the potential mechanisms in SSCs of the m. quadriceps femoris is dependent on the contraction intensity and the type of activation.